Whose school is it? : women, children, memory, and practice in the city - Halperin, Rhoda H. (Louann Atkins Temple women & culture series ;, 2006)
Whose School Is It?: Women, Children, Memory, and Practice in the City is a success story with roadblocks, crashes, and detours. Rhoda Halperin uses feminist theorist and activist Gloria Anzaldúa's ideas about borderlands created by colliding cultures to deconstruct the creation and advancement of a public community charter school in a diverse, long-lived urban neighborhood on the Ohio River. Class, race, and gender mix with age, local knowledge, and place authenticity to create a page-turning story of grit, humor, and sheer stubbornness. The school has grown and flourished in the face of daunting market forces, class discrimination, and an increasingly unfavorable national climate for charter schools. Borderlands are tense spaces. The school is a microcosm of the global city. Many theoretical strands converge in this book--feminist theory, ideas about globalization, class analysis, and accessible narrative writing--to present some new approaches in urban anthropology. The book is multi-voiced and nuanced in ways that provide authenticity and texture to the real circumstances of urban lives. At the same time, identities are threatened as community practices clash with rules and regulations imposed by outsiders. Since it is based on fifteen years of ethnographic fieldwork in the community and the city, Whose School Is It? brings unique long-term perspectives on continuities and disjunctures in cities. Halperin's work as researcher and advocate also provides insider perspectives that are rare in the literature of urban anthropology.